The effect of prenatal yoga on accelerated delivery of TM III pregnant women in the work area Sidomulyo Health Center, Bengkulu - Maulani, Nurul; Putri, Poppy Siska; Mayumi, Chikita (Science Midwifery, 2024)
For the duration of the birthing method, not all mothers' births go easily due to the fact the opportunity of conditions outdoor ordinary limits (pathological) nevertheless exist, together with extended exertions and extended second stage. extended exertions are labor that lasts greater than 24 hours in primi and 18 hours in multi. extended exertions have an effect on the mother and fetus as well as the excessive rate of segment cesarean transport. extended hard work takes place due to the fact the primary and second degrees close longer, so there may be a prolonged lively section which can be used for prolonged labor. The intention of this research is: To discover the impact of prenatal yoga at the acceleration of labor of pregnant women inside the 1/3 trimester within the paintings place of the Sidomulyo medical institution, Bengkulu metropolis in 2024. technique: Quantitative studies with a quasi -experimental research design approach with a manage organization method. The study population was TM III primigravida pregnant girls who had been anticipated to give beginning in February 2024, a pattern of 32 TM III pregnant girls who did prenatal yoga, general sampling approach. data analysis turned into achieved the usage of statistical checks the usage of the independent t check. research results: The common (suggest) acceleration of the second degree of exertion in primigravida moms who took part in prenatal yoga turned into 29.95 minutes. The common (imply) acceleration of the second level of exertions in primigravida moms who did not participate in prenatal yoga was 55.72 minutes. conclusion: there is a power of prenatal yoga at the acceleration of hard work for TM III pregnant women (p-value = 0.000). TM III pregnant ladies can perform prenatal yoga as an opportunity training for childbirth, as it enables intellectual readiness, enables cognizance of the thoughts, provides calm and comfort with a view to accelerate the second stage of exertion.